2015
DOI: 10.1021/es505876k
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Old and Emerging Flame Retardants in Chinese Forest Soils: Sources, Trends and Processes.

Abstract: The levels and distribution of polybrominated diphenylethers (PBDEs), novel brominated flame retardants (NBFRs) and Dechlorane Plus (DP) in soils and their dependence on environmental and anthropological factors were investigated in 159 soil samples from 30 background forested mountain sites across China. Decabromodiphenylethane (DBDPE) was the most abundant flame retardant (25-18,000 pg g(-1) and 5-13,000 pg g(-1) in O-horizon and A-horizon, respectively), followed by BDE 209 (nd-5900 pg g(-1) and nd-2400 pg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 60 publications
5
34
2
Order By: Relevance
“…Previous study has reported that DBDPE concentration was higher than BDE-209 in the background forest soil (Zheng et al, 2015). In contrast, we found no consistent relationships between DBDPE and BDE-209.…”
contrasting
confidence: 99%
“…Previous study has reported that DBDPE concentration was higher than BDE-209 in the background forest soil (Zheng et al, 2015). In contrast, we found no consistent relationships between DBDPE and BDE-209.…”
contrasting
confidence: 99%
“…The chemical DBDPE, which is used as a replacement for BDE 209, was detected in all the sediment samples, thus indicating that this contaminant was prevalent in river and marine sediments in northern China. It is note worthy that concentrations of DBDPE in most of the sediments were higher than levels of BDE 209 in this study, and this phenomenon was also seen in other studies of marine, sludge, and sediment samples (Baron et al, 2013;Lee et al, 2014c;Zheng et al, 2015). The concentrations of DBDPE in 51 coastal and 3 river sediment samples ranged from 1.13 to 49.9 ng g À1 dw (mean: 29.4 ng g À1 dw) and from 0.16 to 39.7 ng g À1 dw (mean: 2.09 ng g À1 dw), respectively.…”
Section: Concentrations and Comparisons With Other Studiessupporting
confidence: 86%
“…On the Jia et al, 2011, 2012b, Qi et al, 2010, Salamova and Hites, 2011, Venier et al, 2014, Wu et al, 2010, Xiang et al, 2014. , Newton et al, 2015, 2010b, Yu et al, 2010, Zheng et al, 2015b. Fig.…”
Section: Soil Sediment and Sewage Sludgementioning
confidence: 98%
“…Qiu and Hites (2008) also found that the highest DP concentrations in tree barks were N100 ng g −1 in the city of Niagara Falls, and dropped rapidly with distance from the production site, suggesting that OxyChem in Niagara Falls was the main DP contributor to the surrounding areas. In China, DP concentrations showed the highest levels in various matrices around the DP facility (Anpon) and soil concentrations surrounding the facility decreased by an order of magnitude within 7.5 km Zheng et al, 2015b). Zhang et al (2013) assessed the occupational exposure to DP and found that DP concentrations were the highest in the blood and hair of workers in the plant, suggesting an evident occupational exposure of manufacturing workers to DP.…”
Section: Dp Productionmentioning
confidence: 99%